Navigating curriculum reform: Approaches and challenges of academic leaders in Malaysian higher education - Kumar, Menaga; Singh, Gurdip Kaur Saminder; Yunos, Farah Naaz Abd (Edelweiss Applied Science and Technology, 2025)
The study explores the roles, approaches, and challenges faced by academic leaders in managing curriculum change and innovation in higher education institutions. A qualitative multiple-case design was employed for this study, where each leader from four mature private higher-education institutions was invited to participate in semi-structured interviews. Data were analyzed using Braun and Clarke’s Reflexive Thematic Analysis with iterative coding aligned to the two research questions of this study, which discuss the approaches used to manage curriculum change and innovation, as well as obstacles or resistance faced during implementation. Overall, the study highlighted that academic leaders occupy a pivotal position in steering curriculum initiatives, ensuring alignment with regulatory requirements, and responding to evolving industry and educational demands. However, despite the structured and participatory approaches adopted, the study revealed several persistent obstacles that hinder effective curriculum implementation, including limited staffing and resources, time constraints, lengthy approval processes, technology gaps, and insufficient stakeholder engagement. The findings of this study underscore that successful curriculum reform in higher education relies on institutional commitment, inclusive stakeholder engagement, efficient processes, and strong leadership. Future research is needed to explore these dynamics across diverse contexts and digital transformations.